Optimization strategy and control technology of four-port SOP for distribution network with PV and BESS - Zhao, Xingjian; Gao, Xiongying; Zhou, Xin; Gao, Feng (Frontiers in Energy Research, 2023)
This paper proposes a four-port soft open point (FSOP) with photovoltaic (PV) and battery energy storage systems (BESS) and its optimization strategy and control technology. Combining PV output, BESS characteristics, peak and valley electric charges, transformer operation efficiency, and soft open point (SOP) characteristics, the operation criteria under different operating conditions are formulated to improve the economy of the distribution network. In this paper, the power distribution optimization algorithm is established based on the transformer consumption characteristic model and the equal consumption incremental rate criterion to improve the power utilization rate and the system’s economy. The system doesn’t require an additional central controller and transmits control signals through the DC link of FSOP to realize the coordinated operation of all ports. The simulation results show that the system and the optimization strategy can realize the system's coordinated operation and improve the distribution network's economy.